2018
DOI: 10.3126/on.v16i1.22122
|View full text |Cite
|
Sign up to set email alerts
|

Effect of red algal bloom on growth and production of carps

Abstract: An experiment was carried to assess the effect of red algal bloom on growth and production of carp, water quality and profit from carp for 120 days at Aquaculture Farm of Agriculture and Forestry University, Chitwan. The experiment included two treatments: carp polyculture in non-red pond and carp polyculture in red pond with algal bloom each with three replicates. Carp fingerlings were stocked at 1 fish/m2 and fed with pellet containing 24% CP at 3% body weight. Net yield of rohu was found significantly highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 6 publications
2
8
0
Order By: Relevance
“…Since the NFY is derived by deducting total stocking weight from total harvesting weight, higher total stocking weight decreased NFY in T1 and T2. When NFY of carp in T1 in the present study was compared with carp polyculture research conducted during wet period in the Aquaculture Farm at AFU, it was found that NFY of carp was similar to that reported by Mandal et al (2018) fed with pellet (24% CP) and higher than Jha et al (2018) fed with farm made supplementary feed. This indicated that pellet is appropriate for dry period over supplementary feed.…”
Section: Discussionsupporting
confidence: 78%
“…Since the NFY is derived by deducting total stocking weight from total harvesting weight, higher total stocking weight decreased NFY in T1 and T2. When NFY of carp in T1 in the present study was compared with carp polyculture research conducted during wet period in the Aquaculture Farm at AFU, it was found that NFY of carp was similar to that reported by Mandal et al (2018) fed with pellet (24% CP) and higher than Jha et al (2018) fed with farm made supplementary feed. This indicated that pellet is appropriate for dry period over supplementary feed.…”
Section: Discussionsupporting
confidence: 78%
“…A total of four classes of phytoplankton, viz. Euglenophyceae, Chlorophyceae, Bacillariophyceae and Cyanophyceae were identified, and among them Euglenophyceae were dominant in red bloom treatment (Mandal et al, 2016(Mandal et al, , 2018. Euglenophytes contributed 61.5% of the total phytoplankton population in the treatment.…”
Section: Discussionmentioning
confidence: 97%
“…Euglena spp. including E. sanguinea inhibits the growth of other beneficial algal groups such as chlorophytes and bacillariophytes (Xavier et al, 1991;Rahman et al, 2007Rahman et al, , 2012Mandal et al, 2018) which are preferred natural food of silver carp and rohu (Siddiquee et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Red scum of Euglena sanguinea on water surface and often in carp polyculture ponds is a common occurrence (Mandal et al, 2016;2018). Euglena sanguinea is a flagellated, unicellular algae found in high nutrient containing freshwaters (Ohio, 2013;Cimoli, 2014;Mandal et al, 2016Mandal et al, , 2018. The occurrence of red colour is due to presence of carotenoid astaxanthin pigments in the cytoplasm (Grung & Liaaen-Jensen, 1993;Gerber & Häder, 1994;Frassanito et al, 2008;Laza-Martínez et al, 2019, Zheng et al, 2020.…”
Section: Introductionmentioning
confidence: 99%